The pharmacology of selective inhibition of COX-2 - Grosser, Tilo (Thrombosis and Haemostasis, 2006)
Selective inhibitors of cyclooxygenase (COX)-2 were developed to improve the safety of anti-inflammatory therapy in patients at elevated risk for gastrointestinal complications which are thought to be caused primarily by depression of COX-1 derived mucosal prostanoids. They were not expected to be more efficacious analgesics than compounds acting on both cyclooxygenases, the traditional (t) non-steroidal antiinflammatory drugs (NSAIDs). While these predictions were generally supported by clinical evidence, an elevated rate of severe cardiovascular complications was observed in randomized controlled trials of three chemically distinct COX-2 selective compounds. The cardiovascular hazard is plausibly explained by the depression of COX-2 dependent prostanoids formed in vasculature and kidney; vascular prostacyclin (PGI2) constrains the effect of prothrombotic and atherogenic stimuli, and renal medullary prostacyclin and prostaglandin (PG) E2 formed by COX-2 contribute to arterial pressure homeostasis. A drug development strategy more closely linking research into the biology of the drug target with clinical drug development may have allowed earlier recognition of these mechanisms and the cardiovascular risk of COX-2 inhibition. Open questions are i) whether the gastrointestinal benefit of COX-2 selective compounds drugs can be conserved by identifying individuals at risk and excluding them from treatment; ii) whether the risk extends to tNSAIDs; iii) and whether alternative strategies to anti-inflammatory therapy with a more advantageous risk-benefit profile can be developed.
Keywords: Clinical studies; atherothrombosis; atherosclerosis; inflammation; inflammatory mediators